A just response the Nation on terrorism, democracy, and September 11, 2001 - Vanden Heuvel, Katrina (Thunder's Mouth Press/Nation Books Distributed by Publisher's Group West, 2002)
"Some of the most respected figures on the progressive left, in a series of thoughtful, informed, and provocative essays, began to analyze the causes and consequences of this new American wound, and spoke out against "Fascism with an Islamic face," jingoism, the undermining of civil rights, phony multilateralism, the confusion between dissent and treason, and articulated a vision of a just response to terrorism." "Others reflected on Osama bin Laden, the concept of "Blowback": modern technological society turned unwittingly against itself, the American right wing's exploitation of a national emergency to further its political agenda, theology versus technology, the futility of space weapons to defend against apocalyptic nihilism, and secular versus fundamentalist Islam. The magazine published dispatches from other countries around the world, and brief background histories of bin Laden's origins, the roots of fundamentalism, asymmetrical warfare, and a press watch." "These selected articles from issues of The Nation, and other sources, are now brought together in book form to counter the bombast and jingoism of so much media coverage since September 11th - while providing informed analysis, provocative commentary, and reasoned debates."--Jacket.